2021
DOI: 10.3389/fped.2021.631547
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, and Laboratory Features of Children With COVID-19 in Turkey

Abstract: Objectives: The aim of this study is to identify the epidemiological, clinical, and laboratory features of coronavirus disease 2019 (COVID-19) in children.Methods: A retrospective study was conducted by pediatric infectious disease specialists from 32 different hospitals from all over Turkey by case record forms. Pediatric cases who were diagnosed as COVID-19 between March 16, 2020, and June 15, 2020 were included. Case characteristics including age, sex, dates of disease onset and diagnosis, family, and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
43
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 21 publications
24
43
3
Order By: Relevance
“…In studies conducted in our country and around the world, it has been reported that the number of male cases is higher than that of girls, and this data is supported by the data of our patients in group I. [ 17 21 ] However, pediatric patients without underlying neurodevelopmental and neuromuscular diseases did not support this data. This difference may be due to the fact that the gender of the patients was not examined according to their comorbidities in other studies or the number of patients with comorbidities was higher than our study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In studies conducted in our country and around the world, it has been reported that the number of male cases is higher than that of girls, and this data is supported by the data of our patients in group I. [ 17 21 ] However, pediatric patients without underlying neurodevelopmental and neuromuscular diseases did not support this data. This difference may be due to the fact that the gender of the patients was not examined according to their comorbidities in other studies or the number of patients with comorbidities was higher than our study.…”
Section: Discussionsupporting
confidence: 78%
“…Although the reported literature information in terms of age distribution is supported by group I, the same is not quite right for group II. [ 17 , 19 , 21 ] The peak of the number of patients over the age of 15 in Group II may be due to the excessive social activity of children in this age group and the increase in this activity with the closure of schools. Another reason may be that there were false opinions in the society, especially among adolescents, that the disease does not affect young people.…”
Section: Discussionmentioning
confidence: 99%
“…Of the total number of patients, 50.3% were male, and more than 80% of all patients had asymptomatic or mild disease. The most common symptoms include fever, cough, fatigue, dyspnea, diarrhea, and stomachache [ 8 ]. The demographic and clinical features of our COVID-19 cases were very similar to those previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that patients with comorbidities such as cardiovascular disease, liver disease, kidney disease, or malignancies are more vulnerable to SARS-CoV-2 infection [ 10 , 11 ]. Correspondingly, a large pediatric cohort from our country revealed an association between having an underlying disease and a severe course of COVID-19 [ 12 ]. However, the course of COVID-19 in patients with a rheumatic disease or those using antirheumatic drugs remains unclear.…”
Section: Discussionmentioning
confidence: 99%